2015
DOI: 10.1016/j.jneuroim.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Transitory loss of glia and the subsequent modulation in inflammatory cytokines/chemokines regulate paracellular claudin-5 expression in endothelial cells

Abstract: Signaling mechanisms involved in regulating blood-brain barrier (BBB) integrity during central nervous system (CNS) inflammation remain unclear. We show that an imbalance between pro-/anti-inflammatory cytokines/chemokines alter claudin-5 expression. In vivo, gliotoxin-induced changes in glial populations and an imbalance between pro-/anti-inflammatory cytokine/chemokine expression occurred as BBB integrity was compromised. The balance was restored as BBB integrity was reestablished. In vitro, TNF-α, IL-6, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 51 publications
3
19
0
1
Order By: Relevance
“…Significance: # p < 0.05 and *p < 0.05 compared with normal control and RE control groups, respectively on esophagus tissue in a RE rat model. The regulating of claudin proteins in the damaged cells and tissue has been reported in experimental gastro-esophageal reflux disease [8,28]. We found that the expression of claudin-4 and claudin-5 were all increased by concentration-dependent and significantly higher in pre-treated ranitidine and geraniin 30 mg/kg group compared with RE control group.…”
Section: Discussionsupporting
confidence: 51%
“…Significance: # p < 0.05 and *p < 0.05 compared with normal control and RE control groups, respectively on esophagus tissue in a RE rat model. The regulating of claudin proteins in the damaged cells and tissue has been reported in experimental gastro-esophageal reflux disease [8,28]. We found that the expression of claudin-4 and claudin-5 were all increased by concentration-dependent and significantly higher in pre-treated ranitidine and geraniin 30 mg/kg group compared with RE control group.…”
Section: Discussionsupporting
confidence: 51%
“…The increased serum IL-6 levels in diabetes mellitus rats were shown to reduce the expression of claudin 5 [ 9 ]. Furthermore, an in vitro study revealed that IL-6 decreased the claudin 5 levels in endothelial cells through the JAK/STAT pathway [ 56 , 57 , 58 ]. Consistent with these findings, the decreased expression levels of claudin 5 in the hippocampus were restored by the IL-6 neutralizing antibody.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that TNF, IL6, IL1β and CCL2 can each induce downregulation of endothelial tight junction proteins in vitro and induce BBB hyperpermeability in vivo [ 14 , 20 , 43 , 47 , 53 , 58 ]. Enhanced paracellular leakage is mediated by downregulation of mRNA of tight junction proteins as shown in our study and in a model of bacterial infection [ 40 ].…”
Section: Discussionmentioning
confidence: 99%